2021
DOI: 10.1007/s40820-021-00773-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Intrinsic Dielectric Properties of Metal Single Atoms for Electromagnetic Wave Absorption

Abstract: Atomically dispersed metals on N-doped carbon supports (M–NxCs) have great potential applications in various fields. However, a precise understanding of the definitive relationship between the configuration of metal single atoms and the dielectric loss properties of M–NxCs at the atomic-level is still lacking. Herein, we report a general approach to synthesize a series of three-dimensional (3D) honeycomb-like M–NxC (M = Mn, Fe, Co, Cu, or Ni) containing metal single atoms. Experimental results indicate that 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Furthermore, the pyridine-type nitrogen atom that was embedded in the carbon lattice structure can improve the conductivity of EDCF, which is easy to migrate and transmit electrons and dissipates the energy of electromagnetic waves through polarization relaxation. Many defects and functional groups containing N, O, and P atoms result in localized states of Fermi level, which is also conducive to the absorption and attenuation of electromagnetic waves [ 74 ]. In the solid-air interface, a large amount of charge in the external electromagnetic field is accumulated, resulting in strong space charge polarization, which plays a positive role in attenuating EMW energy [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the pyridine-type nitrogen atom that was embedded in the carbon lattice structure can improve the conductivity of EDCF, which is easy to migrate and transmit electrons and dissipates the energy of electromagnetic waves through polarization relaxation. Many defects and functional groups containing N, O, and P atoms result in localized states of Fermi level, which is also conducive to the absorption and attenuation of electromagnetic waves [ 74 ]. In the solid-air interface, a large amount of charge in the external electromagnetic field is accumulated, resulting in strong space charge polarization, which plays a positive role in attenuating EMW energy [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that the synergistic effects constructed in N‐doped core‐shell heterojunctions can enhance the EM wave absorption properties at gigahertz. [ 23 ] Moreover, the hetero‐substituted microwave absorbers with 3D structures could thus establish an interconnected network and promote improved dielectric loss capacities, [ 24 ] such as the honeycomb‐like M–N x C, [ 25 ] hollow N‐doped carbon nanoplates, [ 26 ] and N‐doped graphene aerogels. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic (EM) wave absorption materials have attracted considerable attention because of widely applications of electronic devices and communications facilities. [1][2][3][4][5] The EM wave absorption performances are strictly related to the complex permittivity (ε r ) and permeability (μ r ) and their impedance matching, which are mainly associated with dielectric loss capacities, [24] such as the honeycomb-like M-N x C, [25] hollow N-doped carbon nanoplates, [26] and N-doped graphene aerogels. [27] In this study, we achieved various hetero-substitutions in the nitrogen-substituted carbon nanocages (NCNs), including single Fe atoms, subnanometer Fe clusters, and Fe 3 O 4 nanoparticles, by carbonizing the metal-organic frameworks composites under proper temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Interestingly, un-artificial wrinkles within 2D MXene nano-sheets, which are introduced inevitably during the acid etching due to defect-or dislocation-induced stress, have a strong influence on their chemical and electrical properties. [25] Enhanced absorption has been realized in carbon-based materials with the doping of metal single-atoms, [26,27] where the electric dipole can play a key role. [28] Therefore, the effective engineering of wrinkles in MXenes offers new possibilities to construct high-performance EMI shielding films with electric-dipole-induced EW absorption.…”
mentioning
confidence: 99%